2001
DOI: 10.1081/ncn-100002309
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anti-Hiv Nucleoside Inhibitors by Capillary Electrophoresis-Electrospray Ionization Mass Spectrometry

Abstract: A method employing capillary electrophoresis (CE) with tandem mass spectrometry (MS) has been developed for the simultaneous determination, on one hand, of zidovudine (AZT) with stavudine (d4T), and on the other hand, of lamivudine (3TC) with a didanosine metabolite (ddA), four potent human immunodeficiency virus reverse transcriptase (RT-HIV) inhibitors. The influence of several parameters (pH and ionic strength of volatile formic acid-ammonia buffer) as well as the influence of magnesium cation upon electroo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 11 publications
0
20
1
Order By: Relevance
“…The sensitivity of our test is comparable to the liquid chromatography MS/MS analytical method recently described, involving the detection of ddATP by an indirect method with a limit of ddA quantification of 0.1 ng/ml (4 x 10 Ϫ10 M) (1,11). It is important to note that the ddATP content found in our PBMC model (picomole) is much higher than that reported in the literature (femtomole) (18,23,27).…”
Section: Discussioncontrasting
confidence: 37%
“…The sensitivity of our test is comparable to the liquid chromatography MS/MS analytical method recently described, involving the detection of ddATP by an indirect method with a limit of ddA quantification of 0.1 ng/ml (4 x 10 Ϫ10 M) (1,11). It is important to note that the ddATP content found in our PBMC model (picomole) is much higher than that reported in the literature (femtomole) (18,23,27).…”
Section: Discussioncontrasting
confidence: 37%
“…Recently, Benech and co-workers [17][18][19][20][21] used LC-MS/ MS with selected reaction monitoring (SRM) to directly quantitate the intracellular triphosphorylated metabolites of anti-HIV nucleosides, alone or in combination, in human PBMCs of HIV-positive patients. As part of our on going program to develop new bioanalytical methods, our group has previously reported that CE coupled with ESI-MS/MS was an excellent technique for the separation and quantitation of various anti-HIV nucleosides [22,23]. Thus, we turned our attention to the on-line combination of CE with electrospray (ES) MS (CE-MS/MS) for the quantitation of their phosphorylated metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Again, applications in the field of CE-MS dealing with real samples are scarce. Cahours and co-workers [37][38][39], for example, published several papers about the development of a CZE-ESI-MS/MS method for the analysis of the active triphosphate derivates of several NRTIs as their corresponding nucleoside, among a pool of natural nucleosides, however, always using standard solutions. An example does exist, albeit based on spiked samples.…”
Section: Nucleoside Analoguesmentioning
confidence: 99%
“…The traditional approach involves an initial separation of the triphosphate from the other metabolites using ion-exchange cartridges or HPLC, followed by nucleotide dephosphorylation and further quantification of the corresponding nucleoside, leading in return to the concentration of the triphosphate. Quantitation can be accomplished by HPLC-UV [42], HPLC-radioimmunoassay (RIA) [43], RIA [44], enzymatic assay [45], LC-MS/ MS [46,47], and CE-MS/MS [37][38][39]. In the last years, efforts have been made in developing direct methods for the analysis of the active triphosphate metabolites using LC-MS/MS [48][49][50][51], CE-MS/MS [40], and MALDI-time of flight (TOF)-MS [52].…”
Section: Nucleoside Analoguesmentioning
confidence: 99%